PROJECTION APPROXIMATION For WEAKLY SINGULAR INTEGRAL AND INTEGRO- DIFFERENTIAL EQUATIONS - Sharma, Shiva (My University, 2018)
The thesis consists of five chapters. Chapter 1 is the collection of the definitions, natations and some foundamental results which are used in subsequent chapters. In chapter 2, we present an approximate method for the solving the Generalized Abel's integral equations. The approximate method is based on the collecation method for solving volterra integral equations. Generalized Abel's integral equations could be considered as a more general from of volterra integral equations. Collection method in sense of Atkinson's approach is applied to get the approximate solution of Generalize Abel's integral equations
Keywords: PROJECTION; APPROXIMATION; WEAKLY; SINGULAR INTEGRAL; INTEGRO- DIFFERENTIAL; EQUATIONS